Kompetensi Peradilan Pajak di Negara Indonesia Berdasarkan Undang Undang Dasar 1945 - Wishnu Kurniawan; Lendrawati Lendrawati; Siti Nurjanah (Jurnal Selat, 2016)
The most high-income of Indonesia is 75 % derived from Tax. Misappropriation oftax collection came from tax dispute resolution manipulation. Misappropriation of Tax suspected due to unindependently Tax Court in Indonesia. Academic analythical through a philosophical base of absolute competence in upholding its independence Justice in case of Tax Justice .This review based on the analythical method of the absolute competence of the Tax Court with Juridical aspects associated with Philosophical Aspects of the Tax Justice standing. The results will confirmed with the experts' opinion (of Taxation and law, particularly with the Administrative Law and Constitutional Law) The Legal opinion will be analyzing with the provisions of laws and regulations related to the subject matter following the constitution to the level of the basic aspects of the establishment basic norms of legislation. The opinion of the analysis are expected to provide an answer of the Tax Court standing in order to preserve the independence and impartiality of the Tax Court in its function to examine, hear and decide disputes of Tax interference any party. Keyword: Philosophical Aspects, Tax Court, Competences, Independence.